1986
DOI: 10.1159/000146187
|View full text |Cite
|
Sign up to set email alerts
|

A Scanning Electron-Microscopic Study of Femoral Bone Surfaces from Castrate Rats Treated with Dichloromethylene Biphosphonate

Abstract: This study compared SEM appearances of endosteal and periosteal surfaces of anorganic femoral diaphyses from three groups of adult male rats: (1) control; (2) castrate (osteoporotic), and (3) castrate + injections of dichloromethylene biphosphonate (Cl2 entrances; (2) area of vascular canal entrances; (3) number of osteoblast lacunae, and (4) percent area of bone surface types. Endosteal surfaces from untreated osteoporotic rats had significantly more osteoblast lacunae, larger vascular canal entran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The present study and previous studies using scanning electron microscopy (16,17) indicated that clodronate treatment prevents bone loss in adult castrated male rats.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study and previous studies using scanning electron microscopy (16,17) indicated that clodronate treatment prevents bone loss in adult castrated male rats.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the reliability of these markers in reflecting specific changes in osteoclastic activity was assessed by administration of a potent inhibitor of osteoclasts, e.g. the bisphosphonate clodronate (15)(16)(17). The possible relationship between the changes in urinary excretion of biochemical markers and bone mass was determined by the simultaneous monitoring of both parameters in the same rat over time.…”
Section: Introductionmentioning
confidence: 99%
“…The drug is currently used clinically in the treatment of bone metastases of malignant diseases (Jung et al 1983;Douglas et al 1980;Elomaa et al 1983), hypercalcemia due to malignancy (Douglas et al 1980;Cohen et al 1981;Jung et al 1981), Paget's disease of bone (Douglas et al 1980;Delmas et al 1982;Fleisch 1987) and primary hyperparathyroidism (Douglas et al 1980;Shane et al 1981). In addition, there has been interest in its anti-inflammatory action (Flora 1979;Felix et al 1981) and its effect on osteoporosis (Anderson et al 1984;Wink et al 1985;Wink 1986;Mosekilde et al 1987).…”
mentioning
confidence: 99%
“…The samples were placed in 5.25% sodium hypochlorite solution overnight to render them anorganic, dehydrated with acetone and vacuum-dried (Wink, 1982). According to previous observations, the bone turnover is more pronounced on the endosteal surface than on the periosteal surface (Wink, 1986), therefore in this study we observed the endosteal surfaces of the samples . Lateral portions of the sampled bones were glued on specimen stubs, endosteal surface up, ion sputter coated, and viewed at 15 kV using JEOL JSM-T 300 scanning electron microscope.…”
Section: Scanning Electron Microscopy Of Tibiamentioning
confidence: 95%